The admissibility of DNA profiling under Islamic Law of Evidence / Nor Fadzlina Nawi - Nawi, Nor Fadzlina (Universiti Teknologi MARA Kedah, Sungai Petani, 2002)
DNA technology is being increasingly used to offer new solutions to problems that are not easily solved using traditional methods. Continuous development in DNA technology has resulted in masses of technical details, which are often left unchallenged, and yet may contain vital evidence. Hence, this paper wilt highlight the nature and basic principles of DNA and DNA profiling, and the importance of its application in this era of information, communication, and technology. The paper will focus on the issue of the admissibility of DNA profiling under the Islamic Law of Evidence. However, the discussion is rather general and does not focus on any particular type of crime, in order to give a wider view on the matter.